2021
DOI: 10.1002/cft2.20079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating winter malting barley grain yield with fractional green canopy cover

Abstract: Due to growth in the craft brewing industry, farmers in the Eastern U.S. are planting winter malting barley (Hordeum vulgare L.) to meet demands for locally-sourced grain. However, given that barley is a relatively new crop in this region, basic agronomic information relating to stand assessment is needed. This is particularly relevant in this region as climatic variability from extreme temperature fluctuations during the winter and spring can reduce a barley stand, creating the need for farmers to estimate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…This was also evidenced by the green canopy cover during the booting stage. Previous research [84] has shown that Canopeo-measured green canopy cover accounted for 65% of the variability in winter malting barley grain yield. Although the lack of yield penalties remained consistent across both experiments, it appeared that grains spike −1 exhibited a higher value in Larissa, whereas spikes m −2 recorded a higher value in Livadia.…”
Section: Exploring the Feasibility Of A 34% Nitrogen Rate Reduction I...mentioning
confidence: 94%
“…This was also evidenced by the green canopy cover during the booting stage. Previous research [84] has shown that Canopeo-measured green canopy cover accounted for 65% of the variability in winter malting barley grain yield. Although the lack of yield penalties remained consistent across both experiments, it appeared that grains spike −1 exhibited a higher value in Larissa, whereas spikes m −2 recorded a higher value in Livadia.…”
Section: Exploring the Feasibility Of A 34% Nitrogen Rate Reduction I...mentioning
confidence: 94%